Utilitarianism : restorations ; repairs ; renovations : variations on Bentham's master-idea, that disputes about social policy should be settled by statistical evidence about the comparative consequences for those affected - Braybrooke, David (Toronto studies in philosophy., 2004)
"In Utilitarianism: Restorations; Repairs; Renovations, noted Canadian philosopher David Braybrooke revisits Jeremy Bentham's master idea that statistical evidence should determine social policies, and - perhaps surprisingly, given Braybooke's recent championship of natural law - dispels the discredit that standard versions of utilitarianism have invited."--Jacket